CORRELATION BETWEEN C-REACTIVE PROTEIN (CRP) LEVELS AND CHEST CT SEVERITY SCORES IN COVID-19 PATIENTS: A RETROSPECTIVE STUDY - Ravindhra Bharathi; Vijay Prasanth; Saravanan Vaithiyalingam (Journal of Population Therapeutics and Clinical Pharmacology, 2025)
Introduction: CRP levels and Chest CT severity scores, the outcomes of which might prove utilitarian to the clinicians worldwide in the detection, risk stratification as well as early treatment of COVID 19 patients. Objective of the study is to determine the correlation between COVID-19 severity with inflammatory marker CRP and chest CT severity score. Methodology: A hospital based cross sectional study were conducted in a tertiary care for the period of two months from August 2022 to September 2022 by Department of Medicine. The study population was in patients with COVID 19 infection who were tested positive for COVID 19 infection by RT PCR test, whose CRP levels were tested and chest CT imaging done. The sample size was 180 and the sampling technique was simple random sampling. Results: Among 180 participants majority were males (65.6%). Most of the participants belonged to working age group (79%). The most prevalent co morbidity was Diabetes Mellitus (48.9%). The mean CRP level was 57.17 mg/dl with standard deviation of 57.96. The mean Chest CT Severity score was 10.7 with standard deviation of 4.78. The correlation coefficient was found to be 0.26 by Spearman’s rank coefficient method, showing mild positive correlation between Chest CT Severity Scores and CRP levels Conclusion: The present study showed that a weak positive correlation exists between Chest CT Severity Scores and CRP levels (r value=0.26), making it a useful tool for predicting the severity and prognosis of the illness.